Rancang Bangun Pengontrol Efek Gitar Menggunakan Sistem Wireless - Aditya Wahyu Luchmansyaroni (Politeknik Negeri Malang, 2017)
Wireless is a wireless network technology that can be used for voice and data communications. The need for a wireless network system makes the need for technology grow very rapidly starting from communication and data transmission media, one of the technological developments in data transmission media. One of them is in the field of music. Most of the musical instruments such as microphones, bass guitars, acoustic guitars, and electric guitars already use wireless. This can facilitate the movement of these musical players while playing their musical instruments on stage. Therefore, a wireless device for guitar effects is designed that is directly connected to a guitar instrument. This system itself aims to facilitate the movement of guitar players on stage and can also activate guitar effects without the need to step on the guitar pedals at their feet.